2019
DOI: 10.11118/actaun201967010085
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Lactation Stage on Milk Yield, Composition and Renneting Parameters of Milk in Sheep Reared Under Intensive Nutrition

Abstract: The aim of our experiment was to assess changes in milk yield, composition and renneting parameters (pH, titratable acidity, coagulation time and curd quality) of sheep milk in the course of lactation and their relationships in the Lacaune ewes (n = 8), reared under intensive nutrition. The stage of lactation (SL) had a conclusive effect on the daily milk yield (DMY) and contents of all basic milk compounds. The DMY and fat content were relatively high during whole lactation. In our opinion these trends were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…Stage of Lactation. Several authors have reported an increase of fat and protein throughout lactation in ewe milk, although a slight decrease can be observed in mid-lactation (Novotná et al, 2009;Konečná et al, 2019). In agreement with the results from our study, Cipolat-Gotet et al, (2016) reported this same increase in fat and protein concentration at late lactation, as well as a positive correlation of these variables with CY.…”
Section: Categorical Factorssupporting
confidence: 92%
“…Stage of Lactation. Several authors have reported an increase of fat and protein throughout lactation in ewe milk, although a slight decrease can be observed in mid-lactation (Novotná et al, 2009;Konečná et al, 2019). In agreement with the results from our study, Cipolat-Gotet et al, (2016) reported this same increase in fat and protein concentration at late lactation, as well as a positive correlation of these variables with CY.…”
Section: Categorical Factorssupporting
confidence: 92%
“…The values obtained are in line with previous studies for SE sheep milk [29,30]. Several other studies show an increasing tendency in fat and protein content during the lactation period [31][32][33][34][35]. The milk samples analysed showed higher acidity values than the one study [29]; however, the values are in line with those recommended for SE Table 2 shows the statistical significance of flock lactation stage, interaction on the final characteristics of PDO SE cheese.…”
Section: Milksupporting
confidence: 88%
“…The second used approach consisted of linear regressions of individual udder dimension character-Czech Journal of Animal Science, 65, 2020 (11): 424-430 https://doi.org/10.17221/196/2020-CJAS conditions (Mierlita et al 2011;Pesinova et al 2011;Tancin et al 2011;Macuhova et al 2017;Kusza et al 2018). Other results obtained in intensive sheep breeds showed that Lacaune sheep reached higher milk production and fat percentage during a similar period of lactation, while their protein content was on a similar level (Konecna et al 2019). However, previously published results of Konecna et al (2013) obtained in Lacaune sheep, East Friesian sheep and their crossbreds showed very comparable results of milk production or milk components to our study.…”
Section: Statistical Evaluationmentioning
confidence: 99%